Targeting ER-Mitochondria Signaling as a Therapeutic Target for Frontotemporal Dementia and Related Amyotrophic Lateral Sclerosis - Martín-Guerrero, Sandra M.; Markovinovic, Andrea; Mórotz, Gábor M.; Salam, Shaakir; Noble, Wendy; Miller, Christopher C. J. (Frontiers in Cell and Developmental Biology, 2022)
Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are two major neurodegenerative diseases. FTD is the second most common cause of dementia and ALS is the most common form of motor neuron disease. These diseases are now known to be linked. There are no cures or effective treatments for FTD or ALS and so new targets for therapeutic intervention are required but his is hampered by the large number of physiological processes that are damaged in FTD/ALS. Many of these damaged functions are now known to be regulated by signaling between the endoplasmic reticulum (ER) and mitochondria. This signaling is mediated by the VAPB-PTPIP51 “tethering” proteins that serve to recruit ER to mitochondria. Recent studies have shown that ER-mitochondria signaling is itself damaged in FTD/ALS and this can involve breaking of the VAPB-PTPIP51 “tethers”. Correcting disrupted tethering may therefore correct many other downstream damaged features of FTD/ALS. Here, we review progress on this topic with particular emphasis on targeting of the VAPB-PTPIP51 tethers as a new drug target.